Theoretical evaluation on electronic and biological properties of quercetin by quantum chemical and molecular docking method (Journal of Nepal Physical Society, 2024)
The quantum chemical method was used to present the electronic and biological properties of quercetin by enlightening specific reactive sites on the molecule, which demonstrated intra- and intermolecular hydrogen bonding. The geometrical parameters (bond lengths and bond angles) of quercetin were determined and compared to the experimental structure of monohydrate quercetin. The strong intra-molecular hydrogen bond O3-H29… O4 was justified by the quantum theory of atoms in molecules, which was also confirmed by the RDG scatter plot and isosurface. With the global minimum potential at O4 and maximum potential at H31, two groups, OH and C=O, have been investigated as the location for intermolecular hydrogen bonding for solid-state conformation and biological activity. The HOMO–LUMO gap in gaseous and solvent ethanol was measured to be 3.777 eV and 3.932 eV, respectively, confirming that quercetin is more kinetically stable in gaseous medium than solvent ethanol. Global reactivity descriptors provide additional information about the chemical behavior of quercetin in the gaseous and solvent phases. Toxicity measurement predicts that the title molecule will exhibit a third class of toxicity. Molecular docking with the protein aldose reductase reveals that quercetin has the highest binding affinity and the lowest inhibition constant, with the target protein codes 2BGS and 2VDS confirming that it may inhibit aldose reductase.